Study protocol. TRAAPREVIA—TRAnexamic acid for preventing blood loss following a cesarean delivery in women with a placenta pREVIA or low-lying placenta: a multicenter randomized, double blind, placebo controlled trial - Loïc Sentilhes; Hugo Madar; Amélie Ifrah; Jean-Marie Chrétien; Catherine Deneux-Tharaux; the TRAAPREVIA Study Group, the Groupe de Recherche en Obstétrique et Gynécologie (GROG) (BMC Pregnancy and Childbirth)
Abstract Background Placentas that are previa or low-lying are a major cause of severe postpartum hemorrhage (PPH). Tranexamic acid, by inhibiting the fibrinolytic pathway and protecting blood clots from degradation, is a promising drug for preventing blood loss after childbirth, especially in high-risk conditions. It remains unclear whether tranexamic acid would decrease the incidence of severe PPH among women with placentas that are previa or low-lying. Methods and design This multicenter, double-blind, randomized controlled trial with two parallel groups will include 1380 women with placenta previa or a low-lying placenta and a cesarean delivery at a term ≥ 32 weeks, modeled on our previous study of tranexamic acid administered after cesarean deliveries (TRAAP2). Women with high antenatal suspicion of placenta accreta spectrum will not be included. Treatment (either tranexamic acid 1 g or placebo) will be administered intravenously just after birth. All women will also receive a prophylactic uterotonic agent. The primary outcome will be the incidence of a red blood cell transfusion before discharge. This study will have a 90% power to show a 33% reduction in the incidence of transfusion, from 20.0% to 13.4%. Discussion This large multicenter, randomized placebo-controlled trial aims to determine with adequate power if the prophylactic use of tranexamic acid among women with cesarean delivery and a placenta that is previa or low-lying would decrease the incidence of transfusion. Trial registration ClinicalTrials.gov NCT04304625 (March 9, 2020).